1995
DOI: 10.1029/95jb00671
|View full text |Cite
|
Sign up to set email alerts
|

Black‐box modeling of the subglacial water system

Abstract: Measurements of water pressure beneath Trapridge Glacier, Yukon Territory, Canada, yield the following generalizations about subglacial conditions in the studied region: (1) Even over short distances the subglacial water system is highly heterogeneous. (2) The subglacial water system consists of at least two distinct components which we refer to as the “connected” and “unconnected” water systems. (3) Regions of the glacier bed can switch back and forth from being part of the connected or part of the unconnecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
208
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(229 citation statements)
references
References 23 publications
18
208
3
Order By: Relevance
“…8a). During this event, it is likely that there is a transfer of mechanical support for ice shear stresses from high-water-pressure areas with reduced iceb ed coupling (such as site MA) to adjacent areas characterized by lower water pressures and increased ice^bed coupling (Murray and Clarke, 1995;Fischer and Clarke, 2001). In addition, this region would have experienced increased basal shear stress due to longitudinal coupling with fastermoving ice located 140 m further up-glacier at site MA.…”
Section: Further Discussion Of Patterns Of Bed Deformationmentioning
confidence: 99%
“…8a). During this event, it is likely that there is a transfer of mechanical support for ice shear stresses from high-water-pressure areas with reduced iceb ed coupling (such as site MA) to adjacent areas characterized by lower water pressures and increased ice^bed coupling (Murray and Clarke, 1995;Fischer and Clarke, 2001). In addition, this region would have experienced increased basal shear stress due to longitudinal coupling with fastermoving ice located 140 m further up-glacier at site MA.…”
Section: Further Discussion Of Patterns Of Bed Deformationmentioning
confidence: 99%
“…This result is a reminder that spatial gradients in basal water pressure can locally affect the total stress that ice exerts on the bed (e.g. Murray and Clarke, 1995;Lappegard and others, 2006). In 2001 this effect of water pressure on total normal stress was successfully measured and factored into calculations presented hereinafter; this was not possible for the experiment of 2002, in which the earth-pressure cell rotated.…”
Section: Total Normal Stressesmentioning
confidence: 99%
“…Head gradients at the bed adjacent to the tunnel (where boreholes were assumed to connect) reverse as the main tunnel becomes pressurized and unpressurized on a diurnal cycle and the magnitude of the water-level fluctuations in the boreholes dissipates as the boreholes are farther away from the tunnel. Murray and Clarke (1995) showed that load transfer on Trapridge Glacier, Yukon, Canada, occurred when pressure in the channelized system was high, causing a decrease in water level in unconnected boreholes. This was also observed with further study at Haut Glacier d'Arolla (Gordon and others, 1998).…”
Section: Comparison With Other Borehole Arraysmentioning
confidence: 99%
“…Fountain, 1994;Hubbard and others, 1995;Murray and Clarke, 1995;Smart, 1996;Gordon and others, 1998). They typically exist when at least one borehole has a water level that varies only slightly and is considered isolated from (or unconnected with) the channelized drainage system.…”
Section: Borehole Grid Head Gradientsmentioning
confidence: 99%
See 1 more Smart Citation